Dental implications of genetic and congenital intellectual disabilities in Cape Town - Roberts, Tina Sharon (Division of Human Genetics, 2019)
Introduction Intellectual disability (ID) is a common and significant problem which has many social, financial, medical and dental implications in South Africa. The severity of the ID varies, ranging from mild to profound impairment and numerous environmental and genetic factors play a role in the aetiology. Oral health is crucial to the overall health and well-being of children with ID. The dental problems of children with ID may be overshadowed by their intellectual dysfunction, and in some instances, by syndromic manifestations. These dental abnormalities may be unnoticed or considered of lesser importance than systemic health issues. There is a paucity of information in both the international and local scientific literature regarding the dental needs, the dental management implications and barriers to oral care pertaining to children with ID. For these reasons, the principal focus of this thesis is the identification, documentation and analysis of the dental abnormalities a group of children with ID in Cape Town, South Africa. Methodology A total of 206 children with ID were assessed during the investigation; 157 children at six Special Educational Facilities (SE Facilities) and 49 at the Red Cross Children’s Hospital (RXH) in Cape Town. The children were referred to the author by the Medical Genetics team of the University of Cape Town. This clinical study was based on a cross-sectional, quantitative, exploratory, descriptive design. When appropriate, clinical photographs and panorex radiographs were obtained. Signed permission for these records were granted by the parents or legal caregivers. Results The frequency of unmet dental disorders among children with ID both at the SE Facilities and RXH was high: dental caries (67% and 84%); gingival disease (69% and 86%); missing teeth (46% and 51%); malocclusion (30% and 66%); structural tooth abnormalities (7.5% and 38%). Based on clinical observation, forty-three percent of children at the SE Facilities had abnormalities of the jaw and midface that required surgical intervention. Dental fillings were present in only 8% of children at the SE Facilities and 12% of children at the RXH. Many parents and caregivers of children with ID experienced difficulty attending dental clinics. Financial and psychosocial issues were the key barriers that prevented their children from accessing dental services. Conclusions Intellectual disability varies in complexity and affects several South African children. Oral health plays a significant role in the general health and well-being of children with ID. The prevalence of unmet dental needs among children with ID is high, and in South Africa, the limited financial resources dedicated to primary and specialized oral health care may preclude access of many affected children to the required dental services. Furthermore, psychosocial factors such as violence, limited finance, and logistical problems such as transport may also impact on the high frequency of dental disease in this country.